Exceptional preservation of microbial lipids in Paleozoic to Mesoproterozoic sediments - Schwark, Lorenz (Geological Society of America, 2013)
“Biomarker geochemistry” describes a geoscience discipline investigating the molecular and isotopic composition of organic matter preserved in the sedimentary record. Its aim is to utilize structures, functions, and phylogenetic distributions of modern biomolecules in order to elucidate their role in fossil ecosystems.